Subfunctionalization of the Ruby2–Ruby1 gene cluster during the domestication of citrus. (November 2018) - Huang, Ding; Wang, Xia; Tang, Zhouzhou; Yuan, Yue; Xu, Yuantao; He, Jiaxian; Jiang, Xiaolin; Peng, Shu-Ang; Li, Li; Butelli, Eugenio; Deng, Xiuxin; Xu, Qiang
Abstract The evolution of fruit colour in plants is intriguing. Citrus fruit has repeatedly gained or lost the ability to synthesize anthocyanins. Chinese box orange, a primitive citrus, can accumulate anthocyanins both in its fruits and its leaves. Wild citrus can accumulate anthocyanins in its leaves. In contrast, most cultivated citrus have lost the ability to accumulate anthocyanins. We characterized a novel MYB regulatory gene, Ruby2, which is adjacent toRuby1, a known anthocyanin activator of citrus. DifferentRuby2 alleles can have opposite effects on the regulation of anthocyanin biosynthesis.AbRuby2 Full encodes an anthocyanin activator that mainly functions in the pigmented leaves of Chinese box orange.CgRuby2 Short was identified in purple pummelo and encodes an anthocyanin repressor. CgRuby2Short has lost the ability to activate anthocyanin biosynthesis. However, it retains the ability to interact with the same partner, CgbHLH1, as CgRuby1, thus acting as a passive competitor in the regulatory complex. Further investigation in different citrus species indicated that theRuby2 –Ruby1 cluster exhibits subfunctionalization among primitive, wild and cultivated citrus. Our study elucidates the regulatory mechanism and evolutionary history of theRuby2 –Ruby1 cluster in citrus, which are unique and different from that found inArabidopsis, grape or petunia. Primitive, wild and cultivated citrus have different abilities in synthesizing anthocyanins. The subfunctionalization of theRuby2–Ruby1 cluster contributes to the variation and evolution of the anthocyanin biosynthesis regulation in citrus.